2017
DOI: 10.1111/jfbc.12431
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization and antioxidant activity of honey withEragrostisspp. pollen predominance

Abstract: This study aimed to characterize the pollen and physicochemical profiles, and to evaluate the antioxidant capacity of six samples of Moroccan honey. The pollen grains of Eragrostis spp. were predominant in all samples (from a minimum of 46.58 6 1.59% to 72.72 6 2.43% as a maximum), exceeding the minimum (generally 45%) required for the monoflorality nomination of a honey sample, and suggestion a case of newly reported honey. The analyzed samples had low diastase activity and hydroxymethylfurfural (HMF) content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
4
8
0
Order By: Relevance
“…Orange, Barseem and Shesham have same values (47) that contain Extra light amber color while Qurshi honey has Light Amber color. Aazza et al (2018). Boussaid et al, 2018, Khalafi et al, 2016 found the color range between 71.27 mmPfund, 36.64–51.37 mmPfund and 19–45.6 mmPfund, closely resemble the current research.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Orange, Barseem and Shesham have same values (47) that contain Extra light amber color while Qurshi honey has Light Amber color. Aazza et al (2018). Boussaid et al, 2018, Khalafi et al, 2016 found the color range between 71.27 mmPfund, 36.64–51.37 mmPfund and 19–45.6 mmPfund, closely resemble the current research.…”
Section: Resultssupporting
confidence: 88%
“…The proline contents of fresh honey samples were within the codex limit (≥180 mg/kg) and directive 2001/EC (≥180 mg/kg) as compared to branded honey samples. Moloudian et al, 2018, Aazza et al, 2018 and Nayik and Nanda (2015) analyzed the proline content ranged from 240.4 to 848.07 mg/kg, 256.46–924.98 mg/kg and 205.3–551.74 mg/kg respectively, in Iranian and Morocco honey more or less similar to the range of proline content of fresh honeys examined in the current research. The level of proline has been reported to vary depending on the honey flora, but this is more closely associated with the working performance of bees (Manzanares et al, 2014).…”
Section: Resultssupporting
confidence: 81%
“…The colour of honey was evaluated as reported by Aazza et al [16]. A solution of 1 g in 2 mL of distilled water was prepared and the absorbance measured at λ = 635 nm (A 635 ).…”
Section: Estimation Of Honey Colourmentioning
confidence: 99%
“…The colour was determined by measuring the absorbance of the honey solution (1 g in 2 mL of distilled water) at 635 nm (A 635 ), using a UV-Vis spectrophotometer (Ultrospec™ 1100 pro UV/visible spectrophotometer). The mm Pfund values of honey samples were obtained using the following algorithm: mm Pfund = − 38.7 + 371.39 × A 635 (Aazza et al 2017)…”
Section: Estimation Of Honey Colourmentioning
confidence: 99%